# fraction inside brackets

• Feb 7th 2010, 06:22 AM
andyboy179
fraction inside brackets
hi i need to simplify this, Attachment 15290 but i don't know how to so can anyone help please?
• Feb 7th 2010, 09:54 AM
Moo
Hello,

$\left(\frac 23\right)^{-1}=\frac{2^{-1}}{3^{-1}}=\dfrac{\frac 12}{\frac 13}=\frac 12 \cdot \frac{1}{\frac 13}=\frac 12\cdot 3=\frac 32$

(to show as many steps as possible (Giggle)
• Feb 7th 2010, 10:33 AM
andyboy179
Quote:

Originally Posted by Moo
Hello,

$\left(\frac 23\right)^{-1}=\frac{2^{-1}}{3^{-1}}=\dfrac{\frac 12}{\frac 13}=\frac 12 \cdot \frac{1}{\frac 13}=\frac 12\cdot 3=\frac 32$

(to show as many steps as possible (Giggle)

i know a bit of that but i don't understand how Attachment 15293, please explain
• Feb 9th 2010, 06:11 AM
BabyMilo
Quote:

Originally Posted by andyboy179
i know a bit of that but i don't understand how Attachment 15293, please explain

you should know

$\frac{a}{b} / \frac{c}{d}$

$= \frac{a}{b} * \frac{d}{c}$

$\rightarrow$

$\frac{1}{2} / \frac{1}{3}$

$= \frac{1}{2} * \frac{3}{1}$